2010
DOI: 10.1007/s10616-010-9284-y
|View full text |Cite
|
Sign up to set email alerts
|

Application of autologous periosteal cells for the regeneration of class III furcation defects in Beagle dogs

Abstract: The aim of this study was to evaluate the healing of class III furcation defects following transplantation of autogenous periosteal cells combined with b-tricalcium phosphate (b-TCP). Periosteal cells obtained from Beagle dogs' periosteum explant cultures, were inoculated onto the surface of b-TCP. Class III furcation defects were created in the mandibular premolars. Three experimental groups were used to test the defects' healing: group A, b-TCP seeded with periosteal cells were transplanted into the defects;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 17 publications
2
18
0
Order By: Relevance
“…[3][4][5] MSC from various tissues have been investigated for cell-based regeneration of periodontal tissues, including the periodontal ligament, 6-8 bone marrow, [9][10][11] adipose tissue, 12 and periosteum. [13][14][15] Cultured stem cells from the periodontal ligament (PDLSCs) possess characteristics of MSC such as cell surface MSC marker expression (CD105 + , CD90 + , CD44 + , CD73 + , CD45 -, CD31 -, and CD34 -) and multilineage differentiation ability (i.e., into osteoblasts, chondrocytes, and adipocytes). [16][17][18] In addition to MSC characteristics, PDLSCs have unique properties to form a cementum/ periodontal ligament complex-like structure when ectopically transplanted in animals.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] MSC from various tissues have been investigated for cell-based regeneration of periodontal tissues, including the periodontal ligament, 6-8 bone marrow, [9][10][11] adipose tissue, 12 and periosteum. [13][14][15] Cultured stem cells from the periodontal ligament (PDLSCs) possess characteristics of MSC such as cell surface MSC marker expression (CD105 + , CD90 + , CD44 + , CD73 + , CD45 -, CD31 -, and CD34 -) and multilineage differentiation ability (i.e., into osteoblasts, chondrocytes, and adipocytes). [16][17][18] In addition to MSC characteristics, PDLSCs have unique properties to form a cementum/ periodontal ligament complex-like structure when ectopically transplanted in animals.…”
Section: Introductionmentioning
confidence: 99%
“…β‐TCP possesses a porous structure and prominent bioresorbable properties. Bone‐like tissue was successfully formed in nude mice, 20 and Class III furcation defects were repaired in beagle dogs 41 using β‐TCP. Therefore, porous β‐TCP was used for the in vivo experiments in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports used on ceramic and synthetic polymers in periodontal regeneration. However, biomaterials might cause rejections and foreign‐body reactions, which might have a negative impact on expected outcomes.…”
Section: Combined Approaches For Periodontal Regeneration With Periodmentioning
confidence: 99%
“…94,95 In their study, Tsunmanuma et al showed that canine periodontal ligament cell sheets combined with a mixture of beta tricalcium phosphate and collagen enhanced the cementum and periodontal ligament fiber formation in a canine 1-wall defect model. 77 There have been reports used on ceramic 96,97 and synthetic polymers 98,99 in periodontal regeneration. However, biomaterials might cause rejections and foreign-body reactions, which might have a negative impact on expected outcomes.…”
Section: Combined Approaches For Periodontal Regeneration With Periodmentioning
confidence: 99%